Therapeutic Bronchoscopy In The Management Of Central Airway Obstruction: Experience In Fundacion Valle Del Lili, A University Hospital Of Reference In Latin America (2016)
The Central Airway Obstruction (CAO) has malignante and non-malignat causes; the most frequent is pulmonary cancer. Usually present cough and progressive dyspnea, even respiratory failure. Therapy must ensure and restore the airway. The chosen technique depends on the cause, type and severity of the lesion, as well as the technological availability and operator’s ability. Our objective is to describe the experience in Therapeutic Bronchoscopy in Fundación Valle del Lili.